Applied corporate finance : questions, problems and making decisions in the real world - Pyles, Mark K. (Springer Texts in Business and Economics,, 2014)
Applied Corporate Finance fills a gap in the existing resources available to students and professionals needing an academically rigorous, yet practically orientated, source of knowledge about corporate finance. Written by an expert in investment analysis, this textbook leads readers to truly understand the principles behind corporate finance in a real world context from both a firm and investor perspective.  The focus of this text is on traditional theory applied to a holistic business case study, offering readers both a quantitative and qualitative perspective on such topics as capital budgeting, time value of money, corporate risk, and capital structure.  Each section in the book corresponds to the order in which a business makes key financial decisions-as opposed to level of difficulty-allowing readers to grasp a comprehensive understanding of the corporate financial life cycle.  Directly addressing the area of corporate finance in an applied setting, and featuring numerous case examples and end-of-chapter discussion questions and problems, this textbook will appeal to advanced undergraduates majoring in finance, graduate-level students, as well as professionals in need of a quick refresher on corporate financial policy.